Sister Mary Joseph Nodule as a First Manifestation of a Metastatic Ovarian Cancer - Giannina Calongos; Mai Ogino; Takatoshi Kinuta; Masateru Hori; Tatsuo Mori (Hindawi Limited, 2016)
A 76-year-old female presented to our hospital with a 2 cm firm, nontender, protuberant umbilical nodule. She received treatment with antibiotics for suspected granuloma, with no improvement after two months. High levels of CA125 as well as an ovarian cyst and intrathoracic and intra-abdominal lesions on imaging studies made us suspect an ovarian cancer with a Sister Mary Joseph nodule (SMJN) and other metastases. A bilateral salpingo-oophorectomy and umbilical and omentum tumor resections were performed and a metastatic ovarian serous adenocarcinoma was diagnosed by histopathology. After surgery, the patient received chemotherapy with paclitaxel, carboplatin, and bevacizumab; however paclitaxel allergy was observed. As a result, chemotherapy continued with carboplatin and bevacizumab every three weeks for a total of 6 courses. Currently, she is still undergoing treatment with bevacizumab and CA125 levels have been progressively decreasing. SMJN is a rare umbilical metastasis which needs to be considered as a differential diagnosis in the presence of an umbilical tumor for prompt treatment initiation.